Effect of frequent kidding on reproductive and productive traits in Shami goats: Salim Omar Raoof1; Kanyaw Ismail Mahmud1 and Younis Ahmad Sheakh Mohamad2 - Raoof, Salim Omar (The Iraqi Journal of Veterinary Medicine, 2018)
The present study was conducted to investigate the effects of frequent kidding on the reproductive and productive traits in Shami (Damascus) goats. The study was carried out in a commercial private farm at Qushtapa district in Erbil, Iraq. Sixty seven Shami goats were involved during the period from July/2013 to May /2016 for the three kidding seasons. The overall means of daily test milk production and seasonal milk production were 1.955 kg and 176.70, respectively. Frequent kidding significantly (P<0.05) affected daily test milk production and seasonal milk production. Total kids born in three kid crops system in two years (accelerating kidding) were 150 compared with75 kids in two kid crop (naturally annual mating system). The total milk production was 5.85 kg in the accelerating kidding system, compared with 4.056 kg achieved through the annual system. Month of test, age of does, sex and type of birth and weight of does at kidding had exhibited significant effects on daily test milk production and seasonal milk production. Daily milk production was higher during the third month (2.004kg) compared with those obtained from the second (1.957 kg) and first (1.903 kg) months of test. Daily test milk production produced by does at about 5 years old was higher (2.079 kg) than that produced from younger goats (1.634 kg). Daily test milk production of does which gave males were higher (1.943kg), recorded significant at the level (P<0.01) than does which gave females (1.777kg). Does weighting over 60 kg at kidding produced 1.933 kg of milk compared with does weighting less than 50 kg (1.819 kg). Repeatability estimate obtained for daily test milk production was 0.64. It can be concluded that the performance of animals in the three kidding in two years of Shami goat was more beneficial for farmers and provided more milk and meat.